2021
DOI: 10.1093/cid/ciab445
|View full text |Cite
|
Sign up to set email alerts
|

Significant Impact of Coronavirus Disease 2019 (COVID-19) on Human Immunodeficiency Virus (HIV) Care in Hospitals Affecting the First Pillar of the HIV Care Continuum

Abstract: During COVID-19 lockdown, the in-hospital number of HIV indicator conditions decreased disproportionally compared to other non-COVID-19 diseases which was accompanied by reduced HIV testing rates, number and proportion of positive HIV tests, and new HIV referrals with more late presentation after lockdown cessation, indicating a significantly impacted HIV care continuum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…This reduction is particularly remarkable because of the high testing rates of the participants in this cohort before the COVID-19 pandemic (92.0% and 80.9% completed testing for HIV and renal functioning in the past 3 months respectively). Other studies conducted in the Netherlands have found similar reductions in testing for HIV and STIs [ 6 , 11 , 21 ]. Xiridou et al conducted a modeling study on the effect of decreased testing among MSM in the Netherlands, during the pandemic [ 18 ].…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…This reduction is particularly remarkable because of the high testing rates of the participants in this cohort before the COVID-19 pandemic (92.0% and 80.9% completed testing for HIV and renal functioning in the past 3 months respectively). Other studies conducted in the Netherlands have found similar reductions in testing for HIV and STIs [ 6 , 11 , 21 ]. Xiridou et al conducted a modeling study on the effect of decreased testing among MSM in the Netherlands, during the pandemic [ 18 ].…”
Section: Discussionmentioning
confidence: 56%
“…Disruptions of HIV treatment and prevention due to the pandemic have been reported along the prevention cascade [ 2 , 21 ]. During the first lockdown measures (13th of March to 31st of May 2020), essential healthcare was prioritized.…”
Section: The Dutch Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…2 The care for HIV and comorbidities has been further affected by interrupted services because of the COVID-19 pandemic. [16][17][18] Now, the escalation of war in Ukraine jeopardises HIV and AIDS care and drastically disrupts HIV care services. 19,20 As united European HIV experts, including the European AIDS Clinical Society (EACS) and EACS Young Investigators (YING), we state that the full-scale Russian invasion has destabilised the European continent and is an unacceptable threat to the care for people with HIV in Ukraine.…”
Section: Introductionmentioning
confidence: 99%
“…On average, approximately 30 participants have been enrolled each year, with the exception of 2020, during which HIV testing, diagnosis and NOVA enrolment was strongly reduced due to the COVID-19 pandemic. 49 Median duration of follow-up is 2.4 (IQR 1.4-3.1) years. The distribution of participants among Fiebig stages is as follows: Fiebig I, 3 (2.1%); II, 20 (14.3%); III, 7 (5.0%); IV, 49 (35.0%); V, 39 (27.9%); VI, 22 (15.7%).…”
Section: Baseline Characteristicsmentioning
confidence: 99%